EU break-up? Mapping plausible pathways into alternative futures - Niclas Meyer (London School of Economics and Political Science (LSE), European Institute, 2018)
Following Brexit, the rise of populist Eurosceptics across the EU, Central Eastern Europe's flirtation with 'illiberal democracy' and the sovereign debt crisis, which essentially still remains unresolved ten years after it started, even some of the EU's most enthusiastic supporters are today wondering whether the EU could actually break apart. In the paper, I propose the scenario-planning method to address this question and to think about the future of the EU in a structured way. While the method is already well established in the study of socio-technical systems, the paper tests its transferability to the political economy of the EU. Along two drivers, the material struggle to tame globalization and the ideational struggle to fill the void that is resulting from the deconstruction of neoliberalism, the paper maps four plausible pathways into alternative futures. I conclude with a discussion of the potential of scenario-planning to improve the transfer of knowledge from academia into practice.
Keywords: 330; EU; future; neoliberalism; populism; inequality